Gender Dysphoria in children and young people: The implications for clinical staff of the Bell V's Tavistock Judicial Review and Appeal Ruling. Issue 9 (9th December 2021) - Helyar, Sinead; Jackson, Laura; Patrick, Leanne; Hill, Andy; Ion, Robin
Summary: In the past few years, there has been a very significant rise in the number of children and young people seeking treatment for gender dysphoria This area is the subject of much discussion, as evidenced in a recent court case in the UK which examined competence and capacity of young people to consent to potentially irreversible interventions. Clinicians involved in gaining consent to puberty blockers for gender dysphoric young people, must understand the evidence in this area and be aware of the heavy burden of accountability placed upon them.